Psychological Well-Being of Older Adults With Cognitive Deterioration During Quarantine: Preliminary Results From the GeroCovid Initiative - Coin, Alessandra; Devita, Maria; Trevisan, Caterina; Biasin, Francesca; Terziotti, Camilla; Signore, Susanna Del; Fumagalli, Stefano; Gareri, Pietro; Malara, Alba; Mossello, Enrico; Volpato, Stefano; Monzani, Fabio; et al. (Frontiers in Medicine, 2021)
Objectives The spread of COVID-19 has undeniably unsettled the social, psychological and emotional life of the entire world population. Particular attention should be paid to older adults with dementia, given their vulnerability to emotional stressors. The aim of this retrospective study is to evaluate the impact of the first wave quarantine related to Covid-19 on psychological and affective well-being of older adults with mild/major neurocognitive disorders and of their caregivers. Methods Data on participants’ assessment before the quarantine (PREQ) were retrospectively collected. Patients with Mild Cognitive Impairment (MCI) or dementia were recruited from different Centers for Cognitive Decline and Dementia in Italy. During the quarantine, psychological and affective well-being were evaluated by phone through the administrations of scales measuring anxiety and depression (DASS), perceived stress (PSS), coping strategies (COPE) and the caregivers’ burden (CBI). The scales’ results were compared across participants’ PREQ cognitive level (Mini Mental State Examination, MMSE 25, 23-24, and ≤22) with multiple linear regression models. Results The sample included 168 patients (64% women) with a mean age of 79±7 years. After adjusting for potential confounders, more severe cognitive impairment was independently associated with higher DASS and PSS score, and poorer coping strategies (p<0.05). Cognitive functioning was also inversely associated with CBI. Conclusions The impact of the quarantine on the psycho-affective wellbeing of individuals with MCI and dementia and on caregivers’ burden varies according to the PREQ cognitive functioning with more severely impaired patients having worse outcomes.